Формування системи місцевого управління в Україні (1990-2010 рр.) - Євсєєва, Галина Петрівна; Кривчик, Геннадій Георгійович (Дніпропетровський регіональний інститут державного управління Національної академії при Президентові України, м. Дніпро, 2019)
UK: Аналізується розвиток місцевого самоврядування за період двадцятиліття після проголошення незалежності в контексті внутрішньої політики і змін форм державного правління в Україні. Розглядаються позитивні й негативні результати формування демократичної європейської моделі місцевого управління.

RU: Анализируется развитие местного самоуправления за период двадцатилетия после провозглашения независимости в контексте внутренней политики и изменений форм государственного правления в Украине. Рассматриваются положительные и отрицательные результаты формирования демократической европейской модели местного управления.

EN: The scientific and practical problem of developing democratic foundations of local self- government is very important. This problem is devoted to many publications of Ukrainian scholars in the field of political science, public administration, and history. However, unfortunately, most of the works lack a critical view of the practice of domestic state-building. Also, the development of self-government is often depicted in isolation from the internal policy of the state, the struggle for power in it. The development of local self-government in the first decade after the proclamation of independence is considered in this article in the context of domestic policy and changes in the forms of government in Ukraine. It has been shown that many attempts to introduce an effective European model of local self-government were not particularly successful. The negative result had both objective and subjective reasons. First, the inheritance of the totalitarian regime of Ukraine remained rigid centralism, as well as the ineradic ability of what is written in the Constitution of the state, and that which is in reality. Secondly, the central government did not really like to get rid of its power sin favor of the regional authorities, and there fore was not interested in the complete break- up of the Soviet model of relations with regional elites. In addition, despite the fact that there was a parliamentary presidential republic in Ukraine (1991 – 2004 – 2010), that is, formally, under the Constitution, the prime minister was considered the first person in the state; in reality, the main powers always belonged to the head of state. The Presidents of Ukraine (regardless of the particular surname) sought to increase these powers, which, obviously, was and is a characteristic feature of Ukrainian political life.
Формирование системы местного управления в Украине (1990 - 2010 гг.)
Formation of a System of Local Government in Ukraine (1990 – 2010)
Г. Кривчик: ORCID: 0000-0001-7504-4575
Keywords: адміністративно-територіальна реформа; місцеве самоврядування; ради народних депутатів; президент; прем'єр-міністр; адміністрація; административно-территориальная реформа; местное самоуправление; Советы народных депутатов; премьер-министр; администрация; administrative and territorial reform; local government; council of people’s deputies; president; prime minister; administration; КУГПІС